Do measures of memory, language, and attention predict eyewitness memory in children with and without autism?. (August 2017) - Henry, Lucy A; Messer, David J; Wilcock, Rachel; Nash, Gilly; Kirke-Smith, Mimi; Hobson, Zoe; Crane, Laura
Background and aims: There are few investigations of the relationship between cognitive abilities (memory, language, and attention) and children's eyewitness performance in typically developing children, and even fewer in children on the autism spectrum. Such investigations are important to identify key cognitive processes underlying eyewitness recall, and assess how predictive such measures are compared to intelligence, diagnostic group status (autism or typically developing) and age. Methods: A total of 272 children (162 boys, 110 girls) of age 76 months to 142 months ( M = 105 months) took part in this investigation: 71 children with autism and 201 children with typical development. The children saw a staged event involving a minor mock crime and were asked about what they had witnessed in an immediate Brief Interview. This focused on free recall, included a small number of open-ended questions, and was designed to resemble an initial evidence gathering statement taken by police officers arriving at a crime scene. Children were also given standardised tests of intelligence, memory, language, and attention. Results & conclusions: Despite the autism group recalling significantly fewer items of correct information than the typically developing group at Brief Interview, both groups were equally accurate in their recall: 89% of details recalled by the typically developing group and 87% of the details recalled by the autism group were correct. To explore the relationship between Brief Interview performance and the cognitive variables, alongside age, diagnostic group status and non-verbal intelligence quotient, multiple hierarchical regression analyses were conducted, with Brief Interview performance as the dependant variable. Age and diagnostic group status were significant predictors of correct recall, whereas non-verbal intelligence was less important. After age, non-verbal intelligence, and diagnostic group status had been accounted for, the only cognitive variables that were significant predictors of Brief Interview performance were measures of memory (specifically, memory for faces and memory for stories). There was little evidence of there being differences between the autism and typically developing groups in the way the cognitive variables predicted the Brief Interview. Implications: The findings provide reassurance that age – the most straightforward information to which all relevant criminal justice professionals have access – provides a helpful indication of eyewitness performance. The accuracy of prediction can be improved by knowing the child's diagnostic status (i.e. whether the child is on the autism spectrum), and further still by using more specific assessments (namely memory for faces and memory for stories), possibly via the input of a trained professional. Importantly, the findings also confirm that whilst children with autism may recall less information than typically developing children, the information they do recall is just as accurate.